It's a London Thing : How Rare Groove, Acid House and Jungle Remapped the City. - Melville, Caspar (Music and Society Ser., 2019)
This book tells the history of the London black music culture that emerged in post-colonial London at the end of the twentieth century; the people who made it, the racial and spatial politics of its development and change, and the part it played in founding London's precious, embattled multiculture.